Consumo de sustancias psicoactivas y su incidencia en la depresión de un hombre de 28 años de edad del cantón Urdaneta - Benites Rojas, Jose Mauricio (2021)
Depressive problems are a mental state that occurs with great frequency in people who consume some type of psychoactive substances. The purpose of this case study is to determine the relationship between the consumption of psychoactive substances and their incidence in the depression of a 28-year-old adult. In the research process, a descriptive-correlational study was carried out; for this reason, a conceptual and bibliographic analysis was applied, which allowed for a more in-depth study of each of the methods, techniques and variables proposed in the case study. To determine the root of the patient's mental problem, instruments such as the Beck depression inventory were used, in which the patient obtained a score of 34, which is interpreted as a severe degree of depression, and the ASSIT V3.0 test determined positive for cannabis consumption with a score of 15, which is interpreted as moderate consumption. The criteria of the DSM5 Guidelines and the ICD 10 Coding System were used to establish the diagnosis. The results were: the patient's health problems arise from the death of his mother, he consumes marijuana twice a week, he lives with his father and siblings from whom he is distanced, he has difficulty concentrating and is in a low state of mind to carry out his daily activities. By virtue of the findings detected, a therapeutic plan was proposed to help him overcome his addiction and improve his mental state.